PELATIHAN DAN KOMPENSASI PENGARUHNYA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. CONNUSA ENERGINDO - Dosen Fakultas Ekonomi Universitas Persada Indonesia YAI, Asri Warnanti (MAJALAH ILMIAH GEMA, 2014)
This study discusses the â Training and Compensation Effect on Employee Perform in PT CONNUSA Energindoâ. Formulation of the problem in this formulation is whether there is an influence of training and compensating employeesâ performance against the PT CONNUSA Energindo author uses causal comparative research methods (Causal - Comperative Research) is the type of research the characteristics of the problem in the form of a causal link two or more variables . Data collection in this study were obtained by distributing questionnaires to the respondents sampled by 30 people. The design of the statistical analysis used is the analysis of the correlation coefficient , coefficient of determination, linear regression , validity, reliability testing and hypothesis testing using SPSS 17 for windows. From the calculation of multiple correlation R obtained figures for 0977 . This shows that there is a positive relationship so that the relationship between training and compensation on employee performance categorized stronger . Based on the results of data processing can be seen that the value of the adjusted coefficient of determination (R Square) is equal to 0.954. It means that 95.4 % of employee performance variable is explained by the independent variables consisting of training and compensation . A percentage of 4.6 % ( 100 % -95.4 % ) is explained by other variables beyond the variables used . From the results of multiple linear regression analysis calculation equation is: Y = 3.503 + 0.120 X1 + 0.812 X2 + Îµ , which means that when the training ( X1 ) and compensation ( X2 ) increases the work performance of employees will increase simultaneously test results obtained from ANOVA values obtained Fcount 278 291 and the value of F table 3.35 . It can be said that the F value > F ie 278 291 > 3:35 with probability ( significance level ) of 0.000 or below than 0.05 . So it can be said that the training and compensation ( together) effect on employee performance. Keywords : Training , Compensation , Employee Job Performance